New evidence from high-resolution computed microtomography of Triassic stem-mammal skulls from South America enhances discussions on turbinates before the origin of Mammaliaformes - Fonseca, Pedro H. M. (2024)
The nasal cavity of living mammals is a unique structural complex among tetrapods, acquired along a series of major morphological transformations that occurred mainly during the Mesozoic Era, within the Synapsida clade. Particularly, non‑mammaliaform cynodonts document several morphological changes in the skull, during the Triassic Period, that represent the first steps of the mammalian bauplan. We here explore the nasal cavity of five cynodont taxa, namely Thrinaxodon, Chiniquodon, Prozostrodon, Riograndia, and Brasilodon, in order to discuss the main changes within this skull region. We did not identify ossified turbinals in the nasal cavity of these taxa and if present, as non‑ossified structures, they would not necessarily be associated with temperature control or the development of endothermy. We do, however, notice a complexification of the cartilage anchoring structures that divide the nasal cavity and separate it from the brain region in these forerunners of mammals.